2009
DOI: 10.1063/1.3077310
|View full text |Cite
|
Sign up to set email alerts
|

Electrode kinetics of Cu–SiO2-based resistive switching cells: Overcoming the voltage-time dilemma of electrochemical metallization memories

Abstract: The kinetics of the switching process in Cu–SiO2-based electrochemical metallization memory cells was investigated as a function of the switching voltage and the SiO2 film thickness. We observe an exponential dependence of the switching rate on the switching voltage and no significant thickness dependence in the range from 5to20nm SiO2. We conclude from our data that the cathodic electrodeposition represents the rate-limiting step of the switching kinetics. The voltage-time dilemma seems to be overcome by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
226
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(239 citation statements)
references
References 16 publications
(11 reference statements)
12
226
0
1
Order By: Relevance
“…5(a). In contrast to conventional nonvolatile devices, 13 V set is largely independent of the voltage ramp rate. Compared to conventional Cu/TaO x /Pt devices, V set is significantly lower for Cu/TaO x /d-Cu/Pt devices, which makes them interesting for low power applications.…”
Section: -2mentioning
confidence: 99%
“…5(a). In contrast to conventional nonvolatile devices, 13 V set is largely independent of the voltage ramp rate. Compared to conventional Cu/TaO x /Pt devices, V set is significantly lower for Cu/TaO x /d-Cu/Pt devices, which makes them interesting for low power applications.…”
Section: -2mentioning
confidence: 99%
“…SiO 2 based RRAM cells have been studied in respect to switching endurance, 3 power consumption, 4 and switching (reduction) kinetics. 5 It has been also demonstrated that at higher temperatures (above 560 C) the initial switching voltage decreases by thermal diffusion of Cu. 6 Nevertheless, a detailed investigation on the WE kinetics and the transport of mass and charge in very thin SiO 2 films are still missing.…”
mentioning
confidence: 99%
“…1,2 The ECM cell consists of an insulator layer sandwiched between two electrodes, in which one is made from an electrochemically active electrode (AE) metal, such as Ag or Cu, and the other is a counter electrode (CE), such as Pt, Ir, W, or Ag. 3,4 Till now, a large number of ECM cells have been reported, employing various insulating materials such as chalcogenides, [5][6][7][8][9][10][11][12][13] oxides, [14][15][16][17][18][19][20][21][22][23][24] amorphous Si (Refs. 25 and 26) and C, [27][28][29][30] and organic materials.…”
Section: Introductionmentioning
confidence: 99%